VEGETABLE RESIDUAL BIOMASS: TECHNOLOGIES OF TRANSFORMATION AND CURRENT STATUS - Patiño Martínez, Pedro Elías (Innovaciencia, 2014)
The vegetable residual biomass is an alternative for energy production worldwide. To carry out the process of transforming waste into energy carrier, the application of technologies that are consistent with the statement in Section IV, Article 2 Kyoto Protocol to the Framework Convention of the United Nations on Climate Change (1998) and specific regulations of each country or region are required. The technologies that can be applied to vegetable residues are well known globally, within these include: the combustion that generates a fuel called bio-oil, gasification mainly generated carbon dioxide and ammonia, pyrolysis generates a combustible gas, and biological processes (fermentation and digestion) which generate ethanol and biogas. Currently in Spain, USA, Brazil and Germany, amongst other countries, policies have been developed in order to encourage the implementation of biomass plants. In Colombia the residual biomass conversion vegetable so far is being tested in scientific research laboratories mainly in institutions of higher education as the IUniversidad Industrial de Santander, Universidad de Antioquia and Universidad Nacional de Colombia, among others.